Why adopt double standards for alien fish and homoeothermic vertebrates? A reply to Fenoglio, Delmastro, and Boano (2018). Issue 1 (1st January 2018) - Tiberti, Rocco
Abstract: In order to mitigate the ecological impact of alien species there is a need to control or eradicate those species that are causing a loss of biodiversity. However, such conservation actions can lack public support. In their editorial to The European Zoological Journal (Vol. 85, pp. 227–228), Fenoglio and co-authors observe that public opinion is little concerned about fish welfare and, therefore, is less likely to oppose alien fish than alien bird and mammal eradications. Alien fish management is presented as a science-driven model to which the management of alien birds and mammals should aspire, and public education is identified as a solution for the social conflicts inherent to alien species management. This reflects the authors' opinion that a unitary, integrally scientific strategy would be the best one to counter biological invasions. However, a more flexible strategy including societal inclinations might be considered too, to avoid sabotage of the conservation actions by several predictable opponents, including animal rights movements. Moving from the latter opinion, the present reply aims at providing additional examples and argumentations on (i) why double or multiple management standards could be the only viable strategy to counter alien species, (ii) why alien fish management is not a good model, and (iii) why education cannot be the only solution for social conflicts inherent to alien species management.